Catabolic rate of low density lipoprotein is influenced by variation in the apolipoprotein B gene. - Demant, T (1988)
This study examines the potential influence of genetic variation on the metabolism of LDL. Restriction fragment length polymorphisms (RFLP) of the gene coding for apo B were identified using the endonucleases Xba I, Eco RI, and Msp I in a group of 19 subjects with moderate hyperlipidemia. There was a significant association between the Xba I polymorphism and the total fractional clearance rate (FCR) of LDL. The individuals with the X1X1 genotype had, on average, a 22% higher FCR (P less than 0.025) than those with the genotype X2X2 (X2 allele = presence of Xba I cutting site). This difference was attributable to increased clearance by the receptor-mediated pathway of LDL catabolism. In this group of subjects, there was no association of LDL kinetic parameters and RFLPs of the LDL receptor gene or the AI- CIII- AIV gene cluster. The data suggest that variation in apo B itself, presumably acting through variable binding to the LDL receptor, makes a significant contribution to the rate of catabolism of LDL.